Physician perceptions and understanding of pet ownership in healthcare compliance and patient well-being: a one health investigation - Kipnis, Faith; McCobb, Emily; Mueller, Megan K.; Gatlin, Meera; Armstrong, Catharina A. (Frontiers in Health Services, 2025)
IntroductionPets contribute positively to human mental and physical health outcomes but can also impose financial obligations and personal responsibilities that may impede pet owners from accessing healthcare services, especially by restricting access to inpatient and long-term care. This preliminary study investigates the complex interplay between pet ownership and healthcare access and compliance through the perspective of physicians, exploring how pets influence their patients’ health.MethodsAn online survey was designed and distributed to physicians in Massachusetts, USA. The survey collected information about participant demographics and their experiences and beliefs surrounding how pets influence physician-client relationships, healthcare access and compliance, and human-animal interactions.ResultsOf 16 physicians surveyed from various specialties, 25% noted that they believe pets can be a barrier to accessing treatment or services among their patients. Many of the participants (56%) reported that they had experienced a patient who declined or resisted recommended treatments or services due to concerns about their pet. The most commonly reported barrier to healthcare was being unable to find pet care. Most participants (63%) agreed that a low or no-cost boarding facility could be an effective solution to address pet-related concerns among their patients. All participants reported that they believe that owning pets has psychosocial benefits.DiscussionFindings from this study indicate that there is a gap in resources available to patients with pet-related concerns that may prevent them from accessing healthcare services and that there is a need for more research on the role of pets in healthcare access and compliance.